2017
DOI: 10.1111/cch.12464
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of primary caregivers of children with cerebral palsy: a comparison between mother and grandmother caregivers in Anhui province of China

Abstract: The quality of life is significantly unsatisfactory in both mother and grandmother primary caregivers of children with CP; this research provides evidence for the need of the monitoring of these caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 21 publications
4
9
1
5
Order By: Relevance
“…The same results were confirmed during 2017 by Wu et al conducting research in China, using SF 36 questionnaires to assess the QOL of mothers of children with cerebral palsy (25). Lee et al (2019), in their study, obtained a very poor value in QOL of mothers of children with cerebral palsy (26).…”
Section: Discussionsupporting
confidence: 60%
“…The same results were confirmed during 2017 by Wu et al conducting research in China, using SF 36 questionnaires to assess the QOL of mothers of children with cerebral palsy (25). Lee et al (2019), in their study, obtained a very poor value in QOL of mothers of children with cerebral palsy (26).…”
Section: Discussionsupporting
confidence: 60%
“…Moreover, studies have shown that as a child's illness progresses, both the child and his or her caregivers experience a deterioration in QOL and a significant decrease in their physical, psychological, social, and economic well-being [14][15][16][17]. Therefore, some studies have aimed to assess the psychosocial factors associated with the QOL of family caregivers within the context of chronic diseases [8,13,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research showed no significant differences in work-family conflict and work-family facilitation between mothers of children with T1D and controls [38]. In the literature, when the grandmother was the primary caregiver, the QOL score was lower than that of mothers of children with other chronic conditions [39]. The QOL perceived by fathers was significantly higher than that of mothers [29].…”
Section: Discussionmentioning
confidence: 78%